The Students’ Perception Towards the Use of Webtoon to Improve Reading Comprehension Skill - Fakhrurriana, Ria; Ma’ruf, Muhammad Hijratul Mahali (Department of English Language Education, UIN Sunan Ampel Surabaya, 2024)
This inquire about examined almost student’s perception on the utilize of Webtoon to move forward reading comprehension ability. Webtoon could be a modern apps that can be utilized to move forward reading skills by its words utilized and captivating pictures. The reason of this think about is to clarify whether or not Webtoon can improve student’s readability in reading comprehension capability. The respondents of the ponder are the understudies of English Instruction understudies at IAIN Kediri.The result of the think about shows that the students are more interested and get the inspiration to progress their reading comprehension capability by utilizing Webtoon.